Understanding seabird behaviour through long term tracking data - Siddiqi-Davies, KR (2023)
Comprehending how organisms maximise their reproductive success in an ever-changing environment lies at the core of animal behaviour studies. However, animals that inhabit highly dynamic habitats often pose challenges for direct observation. Biologging deployments facilitate remote monitoring of animals in otherwise inaccessible environments, particularly pelagic species. In this thesis, I harnessed an extensive geolocator dataset spanning multiple colonies to extract novel behavioural insights concerning the Manx Shearwater (Puffinus puffinus), a procellariform seabird known for its extreme life history strategy. Their remarkable migration across hemispheres to synchronize with seasonal food availability presents a unique array of challenges. Firstly, I unveil the ability of individual shearwaters to plastically adjust their over-wintering distribution in response to the El Niño Southern Oscillation. However, decreased foraging activity during El Niño years initiates carry-over effects on subsequent breeding, resulting in a reduction of chick provisioning efforts. Additionally, I elucidate how shearwaters adjust their southbound migratory patterns based on breeding phenology. Birds that breed later and subsequently postpone their post-breeding migration take shorter duration migrations with fewer foraging stopovers. Notably, these late-departing birds optimize their flight with lunar cycles, strategically utilizing moonlit nights for visually guided flight. Next, I investigate how seasonal fluctuations in photoperiod influence light-limited chick provisioning behaviours. I find that extended daylight promotes increased foraging and provisioning efforts, albeit accompanied by shorter nights, diminishing adults' ability to mitigate predation risks through moonlight avoidance. Lastly, I delve into how sex-specific reproductive roles influence diving behaviour during pre-laying using dive logger deployments. I discern that males exhibit increased diving efforts during pre-laying, and are less able to exploit evening foraging opportunities due to heightened colony attendance for nest defence. I also employed a pioneering DNA metabarcoding analysis of Manx shearwater diet, identifying six distinct fish species consumed by breeding adults. This thesis exemplifies the application of advanced analytical techniques to long-term biotelemetry data, providing valuable insights into individual animal behaviour.